2020
DOI: 10.3389/fnint.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Brain Axis in the Early Postnatal Years of Life: A Developmental Perspective

Abstract: Emerging evidence suggests that alterations in the development of the gastrointestinal (GI) tract during the early postnatal period can influence brain development and viceversa. It is increasingly recognized that communication between the GI tract and brain is mainly driven by neural, endocrine, immune, and metabolic mediators, collectively called the gut-brain axis (GBA). Changes in the GBA mediators occur in response to the developmental changes in the body during this period. This review provides an overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 249 publications
(324 reference statements)
0
57
1
3
Order By: Relevance
“…These pathways play pivotal roles in regulating cellular processes of oxidative stress and immune activation, energy metabolism, and biosynthesis, and also involved in degenerative disorders and aging ( Orlandi et al., 2020 ). These differences may relate to the sex differences in the hypothalamic-pituitary-adrenal (HPA) axis’ response to early life stress among preterm infants, mediated by HPA produced glucocorticoids, cortisol, and other hormones ( Cong et al., 2015 ; Jena et al., 2020 ). Limited studies are discovering gut microbiome metabolism in human infants.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways play pivotal roles in regulating cellular processes of oxidative stress and immune activation, energy metabolism, and biosynthesis, and also involved in degenerative disorders and aging ( Orlandi et al., 2020 ). These differences may relate to the sex differences in the hypothalamic-pituitary-adrenal (HPA) axis’ response to early life stress among preterm infants, mediated by HPA produced glucocorticoids, cortisol, and other hormones ( Cong et al., 2015 ; Jena et al., 2020 ). Limited studies are discovering gut microbiome metabolism in human infants.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes species may play a key role in promoting neurodevelopment during a critical time in late infancy when myelination and expanded connectivity of neuronal networks normally occur; when these processes are slowed, pervasive developmental delay can result. 38,39 With successive increases to gut microbial species richness in both young and older infants, greater connectivity in brain areas that support cognitive development and language acquisition has been reported. 40,41 We observed that presence of the Bacteroidetes-cluster (with the highest species richness of Bacteroidetes), as well as higher relative abundance of genus Bacteroides at 1 year, were associated with improved neurodevelopmental outcomes.…”
Section: B Cluster-1mentioning
confidence: 99%
“…More likely, an early modulation of neurodevelopment which could lead to long-term consequences on brain structure and function may be suspected. Whether early microbiota participates in the development of the central nervous system has been proposed in a series of publications and examined through the observation that key events as microglia proliferation, synaptogenesis, and pruning are impacted in germ-free mice, after antibiotics treatment or after specific fecal transplantation and result in behavioral modifications as anxiety-like symptoms, depression, or autism spectrum disorder ( Goyal et al, 2015 ; Jena et al, 2020 ; Morais et al, 2020 ). Food intake regulation is the result of complex interplays between a large number of structures; therefore, to deepen our knowledge on the impact of early microbiota transfer, we need to go further and perform a detailed anatomical, transcriptomic, and functional analysis of the brain structures (VTA, NAc, HT, and NTS) and the different element of the gut–brain communication that can be disturbed according to the existing microbiota.…”
Section: Discussionmentioning
confidence: 99%